A Bibliometric Analysis of Blended Learning Approaches in English Language Teaching - Sudewi, Putu Wahyu; Wahyuni, Asti; Syahrullah, Syahrullah; Khatimah, Nur Husnil (ENGLISH FRANCA : Academic Journal of English Language and Education, 2025)
This study conducts quantitative bibliometric evaluation to evaluate the advancements and thematic distributions of the research relating to blended learning in English education. This project intends to perform a bibliometric analysis of 2024. Publications indexed in Scopus on blended learning in English education to identify the patterns, trends, and topics of this contemporary research. By collecting and analyzing ten Scopus-indexed articles published in 2024 using tools such as VOSviewer and Publish or Perish, the research maps key patterns in scholarly output, including citation frequency, methodological tendencies, and keyword co-occurrence. The bibliometric data reveal a growing scholarly interest in integrating technology with pedagogical practices to improve English language learning outcomes. Among the ten analyzed articles, diverse methodological approaches were found, including experimental research, bibliometric reviews, case studies, and mixed-methods designs. A broader search indicated a total of 170 related publications within a single year, reflecting the rapid expansion of the field. Keyword network visualization categorized the research landscape into three dominant clusters: practical applications in higher education, foundational research design, and digital learning perceptions. The results show that blended learning's adaptability and the ability to meet various learner needs have enabled it to become a transformative tool in English education. These findings also offer a better grasp of the complexities of research, facilitating future work and the design of policies for teaching and learning in the digital era.